Pengaruh Corporate Governance, Etnis, Dan Latar Belakang Pendidikan Terhadap Environmental Disclosure: Studi Empiris Pada Perusahaan Listing di Bursa Efek Indonesia - Djoko Suhardjanto; Novita Dian Permatasari (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2010)
The purpose of this study is to examine relationship between corporate governance and its environmental disclosures. Corporate governance are identified as the proportion of independent commissioner, the ethnic of commissioner president, the educational background of commissioner president, the number of commissary board meeting, the proportion of independent audit committee, and the number of audit committee meeting. This study includes industry type and firm size as control variable. Companies’ environmental disclosures are measured by using the Indonesian Environmental Reporting index that developed by Suhardjanto, Tower and Brown (2007). Under proportional random sampling method, 90 Indonesian listed companies’ annual reports are selected. From the sample, there is fourthy nine percent (49%) disclosed environmental information with level of five point four percent (5.4%). This study employed a data testing technique: classical assumption, descriptive statistic, and hypothesis test using logistic regression, multiple regression, t-test, and ANOVA. Analysis of statistical results the proportional of independent commissioner, the ethnic of commissioner president and the firm size are as significant predictors to environmental disclosure.